Differences of Schirmer’s Test Result In Patients With Controlled And Uncontrolled Diabetes Mellitus - Atika Hazmi; Riski Prihatningtias; Hesti Triwahyu Hutami; Maharani Cahyono (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Diabetes Mellitus (DM) is a metabolic disease whose prevalence continues to increase every year. Peripheral neuropathy as a microvascular complication of DM can cause dry eye syndrome. HbA1c levels can determine controlled or uncontrolled DM.Objective: To determine the differences of the Schirmer’s test result for patients with controlled and uncontrolled diabetes mellitus.Methods: This study was an analytic observational study with cross sectional design. The study subjects were 44 diabetes mellitus patients consisting of 22 patients with controlled DM and 22 patients with uncontrolled DM who were selected based on inclusion and exclusion criteria, using consecutive sampling method. Data were collected from primary data that consists of name, age, gender, duration of DM, medical history, Hb, MCV, HbA1c and the Schirmer’s test result. The data were analyzed using non parametric Mann Whitney test and p < 0.05 was taken as significance.Results: The Schirmer’s test result < 10 mm which indicated the presence of dry eye syndrome was mostly found in female (71.4%), age > 45 years (85.7%), duration of DM > 10 years (78,6%), and patients with uncontrolled DM. The non parametric Mann Whitney test showed that there was a significant difference in the Schirmer’s test result (p < 0,05) between patients with controlled and uncontrolled DM.Conclusion: The Schirmer’s test result in patients with controlled DM was higher than patients with uncontrolled DM.